PENDAMPINGAN BELAJAR SISWA USIA SEKOLAH DASAR DI PADUKUHAN KAYEN MELALUI PROGRAM MERDEKA BELAJAR KAMPUS MERDEKA - Susanti, Susanti; Fahmi, Muhamad; Himawati, Fety; Nurrohman, Sidiq; Lestari, Tata Sri; Kurnia, Siti Aulia; Maulidah, Sinta Dewi; Fifuadi, Shulhi; Makhfudah, Rizki; Julmiati, Julmiati; Utami, Selly; Farhana, Zada; Darojatun, Khoirunnas; Miyono, Ahmad Kurnia; Ariyani, Yusinta Dwi; Wahyudi, Andi (LPPM Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2022)
One of the problems experienced by the Padukuhan Kayen community is the difficulty of elementary school students in participating in online learning, so that learning assistance is needed for children in elementary school. These problems include not understanding the material, not doing assignments straightforwardly, to the role of parents who are not right in helping students learn at home. The purpose of this activity is to provide learning assistance to students to train academic abilities and master learning objectives, starting from tutoring reading and numeracy, doing assignments, and providing explanations of school materials that are not yet understood.The stages of mentoring carried out include the preparation stage, the socialization stage, and the implementation stage of activities. The location of the mentoring is planned in Kayen Hamlet, Kalurahan Sendangsari, Pajangan, Bantul. The results obtained by students are being able to read and count well, being more active in doing schoolwork, and better understanding learning materials at school.This activity received a very good response from local residents. The children are also very enthusiastic in participating in activities as evidenced by always being present when there is a schedule of guidance and trying to complete the tasks given. At the end of the activity, KKN-T students held a children's quiz competition as an evaluation of the implementation of the activity.